2 a + b 4 c + b + 2 c 4 a + c + a b Let a , b and c be positive reals, find the minimum value of the expression above, submit your answer to 2 decimal places
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The "fiddling" part is the important part of this inequality, which allows us to apply standard approaches that we are familiar with.
I think the equality holds when 2 a = 2 c = b since you've set a = A ; b = 2 B , c = C and the equality holds when A = B = C
@Pi Han Goh Sir, what I did was that I took 2a,b and 2c as A,B and C...........then, I assumed that A+B+C=k (k is a positive real number).......
Now writing the expression in terms of A,B,C and k, we see that it is cyclic, and hence, Jensen's Inequality did the work easily............Is my approach correct??
Log in to reply
I don't see how Jensen's plays a role in this. Please elaborate more on this. Thanks.
Log in to reply
Well, continuing after A,B,C and k,
We need to minimize the cyclic expression (2A)/(k-A) which can be done by Jensen's..........!!
Log in to reply
@Aaghaz Mahajan – I find it hard to follow what you are saying. How can we convert the expression into a cyclic sum? What is the function f used in this Jensen's inequality?
If you're so sure of your work, why don't you present it in a clearer manner? Because it's really hard for anyone to understand brief one-line solutions that doesn't convey much.
Log in to reply
@Pi Han Goh – @Pi Han Goh Sir, I would willingly do that, but I have ZERO knowledge of Latex and Coding in general........I mean, I don't even use computers for doing programming......I only use Brilliant to solve problems and learn new things from the community everyday.........But, I am afraid I can't help people by writing detailed solutions that is why whatever solutions I have written, they are all brief without using Mathematical symbols, so that people can understand it........I apologize for the inconvenience caused to you sir.......
Log in to reply
@Aaghaz Mahajan – Just write it in plain text then.
Call the expresion A , now we see A + 6 = 2 a + b 4 c + 4 a + 2 b + 2 c + b 2 b + 4 a + 4 c + c + a 2 a + 2 c + b ⇔ A + 6 = ( 2 a + 2 c + b ) ( a + 2 b 1 + c + 2 b 1 + c + a 1 ) By Cauchy-Schwarz inequality , we easily prove that A + 6 ≥ 9 ⇔ A ≥ 3 The equality holds when b = 2 a = 2 c
2 a + b 4 c + b + 2 c 4 a + c + a b = 2 a c + b c 4 c 2 + a b + 2 a c 4 a 2 + b c + a b b 2 ≥ 4 a c + 2 b c + 2 a b ( 2 c + 2 a + b ) 2 Let 2 c = x , 2 a = y , b = z .Then the expression becomes: 2 a + b 4 c + b + 2 c 4 a + c + a b ≥ x y + x z + y z ( x + y + z ) 2 Notice that: x 2 + y 2 + z 2 ⟹ ( x + y + z ) 2 ⟹ x y + x z + y z ( x + y + z ) 2 ≥ x y + x z + y z ≥ 3 ( x y + x z + y z ) ≥ 3 Hence: 2 a + b 4 c + b + 2 c 4 a + c + a b ≥ 3 Equality occurs when 2 c = 2 a = b .
Nice observation!
Problem Loading...
Note Loading...
Set Loading...
Let's try to make the expression symmetric first, that is, try to make the values of a , b and c interexchangeable. With a little fiddling (hard to explain this part), let a = A , b = 2 B , c = C , the expression becomes
2 A + 2 B 4 C + 2 B + 2 C 4 A + A + C 2 B = = A + B 2 C + B + C 2 A + A + C 2 B 2 ( A + B C + B + C A + A + C B )
This is a direct application of Titu's lemma , or more specifically Nesbitt's inequality (as shown in the fourth example):
Thus, 2 A + 2 B 4 C + 2 B + 2 C 4 A + A + C 2 B ≥ 2 ⋅ 2 3 = 3 .
So the minimum value of the expression in question is 3 and it occurs when A = B = C or 2 a = b = 2 c ⇒ a = 4 1 , b = 2 1 , c = 4 1 .